Das Stadtklima, seine Stellung in der Klimatologie und Beiträge zu einer witterungs-klimatologischen Betrachtungsweise - Eriksen, Wolfgang (ERDKUNDE, 1964)
After an investigation of the ways in which the concept urban climate has been defined the paper points out the necessity of applying in agreement with the modern concept of climate the weather-climatological point of view also in respect of local climatical, in this case, urban climatical phenomena. By arranging the climatological data according to differing weather periods, precisely identifiable by co-ordinating them with major weather conditions, the climatic means of a local order may be analysed more precisely and results of urban climatical research gained so far enriched. The method allows, according to the complexity of the weather, the elucidation of the interrelationship of different climatic elements. Diagrams are able to illustrate both the role played by single elements on the formation of an urban climate and by the terrain on the spatial distribution of the climatic elements in different weather conditions; furthermore they can visualise the reflexion of these influences in phenological respects.